2020
DOI: 10.1097/tgr.0000000000000277
|View full text |Cite
|
Sign up to set email alerts
|

Boxing to Improve Sleep Quality and Daytime Sleepiness in Individuals With Parkinson Disease

Abstract: The purpose of this study was to determine whether high-intensity exercise boxing has an effect on sleep quality and daytime sleepiness in individuals with Parkinson disease (PD). Fifteen (male: n = 10; female: n = 5) participants with PD completed biweekly high-intensity boxing sessions for 6 weeks. Outcome measures for sleep quality, daytime sleepiness, and depression were taken at baseline, posttraining (7 weeks), and 12 weeks. A repeated-measures multivariate analysis of variance was used to examine change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Throughout the intervention, tolerability data indicated no adverse changes in muscle soreness, a reduction in fatigue, and improvements in sleep. The improvements in sleep align with a recent investigation that noted positive effects on sleep quality and daytime sleepiness following boxing training 22 . These findings suggest that boxing training interventions, including high‐intensity components, are well tolerated and safe for people with PD.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Throughout the intervention, tolerability data indicated no adverse changes in muscle soreness, a reduction in fatigue, and improvements in sleep. The improvements in sleep align with a recent investigation that noted positive effects on sleep quality and daytime sleepiness following boxing training 22 . These findings suggest that boxing training interventions, including high‐intensity components, are well tolerated and safe for people with PD.…”
Section: Discussionsupporting
confidence: 84%
“…The improvements in sleep align with a recent investigation that noted positive effects on sleep quality and daytime sleepiness following boxing training. 22 These findings suggest that boxing training interventions, including high-intensity components, are well tolerated and safe for people with PD.…”
Section: Discussionmentioning
confidence: 80%
“…In kinematics, the angle of the lamb and horse is used to illustrate the stability of the lower limbs and maintain the balance of the body. It is beneficial to increase the hitting effect with the help of the changes in the angle of the body's joints and the ground reaction force [9,10]. e techniques and requirements of Japanese punching boxing: Japanese punching boxing is one of the basic attack methods of Wing Chun [11].…”
Section: The Effect Of Wing Chun Japanese Punchingmentioning
confidence: 99%
“…Preliminary non-randomized controlled studies have highlighted the positive effect of boxing programs on the balance [29,30], mobility [31][32][33], and quality of life [34,35] of people with Parkinson's disease. PD patients who attended boxing programs during the study period reported an improvement in fatigue levels as they felt more energetic, experienced a reduced fear of falling, anxiety, depression, and improved their social lives [36,37]. In addition, they reported a better quality of life than those who had not participated or had previously participated in these programs [26].…”
Section: Introductionmentioning
confidence: 97%